Transmission Efficiency, Preference and Behavior of Bemisia tabaci MEAM1 and MED under the Influence of Tomato Chlorosis Virus - Shi, Xiaobin; Tang, Xin; Zhang, Xing; Zhang, Deyong; Li, Fan; Yan, Fei; Zhang, Youjun; Zhou, Xuguo; Liu, Yong (Frontiers in Plant Science, 2018)
Tomato chlorosis virus (ToCV, genus Crinivirus, family Closteroviridae) is an economically important virus in more than 20 countries. In China, ToCV was first detected in 2013 and has already spread throughout the country. ToCV is transmitted in a semi-persistent manner by the whitefly, Bemisia tabaci, but not seed. In the past two decades, the most invasive MEAM1 and MED have replaced the indigenous B. tabaci in China, and currently MED is the most dominant cryptic species. To better understand the prevalence of ToCV with their vectors, we tested the hypothesis that the rapid spread of ToCV in China is closely related to the dominance of MED. ToCV acquisition and accumulation rate following transmission was significantly higher by MED than MEAM1. In addition, ToCV persisted for more than 4 days in MED but only 2 days in MEAM1. Viruliferous MED preferred non-infected over virus-infected plants, although MED performed better on infected than on non-infected plants. Our combined results support the initial hypothesis that the rapid spread of ToCV is associated with the spread of B. tabaci MED in China.